Application of Discovery Learning and Inquiry Learning Model in Improving Students’ Mathematical Literacy Skills - Putri, Yoshi Ivana; Fakhriyana, Dina (Jurnal Pendidikan Matematika, 2023)
The OECD-PISA results state that the mathematical literacy ability of students in Indonesia is relatively low. The aims of this study were: 1) To find out the increase in mathematical literacy skills by applying the Discovery Learning model, 2) To find out the increase in mathematical literacy skills by applying the Inquiry Learning model, 3) To find out whether mathematical literacy skills are increased by the application of the Discovery Learning model rather than Inquiry Learning.  This study utilized a quantitative approach.  The sampling technique was purposive sampling with two experimental groups in eighth-grade SMPN 1 Bae Kudus.  The experimental group I applied the Discovery Learning model and the experimental group II applied the Inquiry Learning model. The data analysis technique used the t-test and the Mann-Whitney U test. The results of this study were: 1) The t-test has given a significance level of 0,00 < 0,05. This means that there was a significant increase in the mathematical literacy skills of students in the experimental group I after the application of the Discovery Learning model with an increase in N-gain of 71%, 2) The t-test has given a significance level of 0,00 < 0,05.  This means that there was an increase in the mathematical literacy skills of students in experimental group II after applying the Inquiry Learning model significantly with an increase in N-gain of 60%, 3) The Mann-Whitney U test has given a significance level of 0,048 < 0,05 which indicated that literacy skills students' mathematics was further improved by the application of the Discovery Learning rather than Inquiry Learning model. Hasil OECD-PISA menunjukkan bahwa kemampuan literasi matematika siswa di Indonesia relatif rendah. Tujuan penelitian ini adalah: 1) Mengetahui peningkatkan kemampuan literasi matematika dengan penerapan model Discovery Learning, 2) Mengetahui peningkatkan kemampuan literasi matematika dengan penerapan model Inquiry Learning, 3) Mengetahui apakah kemampuan literasi matematika lebih meningkat dengan diterapkannya model Discovery Learning daripada Inquiry Learning. Penelitian ini menggunakan pendekatan kuantitatif. Teknik pengambilan sampel adalah sampling purposive dengan dua kelas eksperimen di kelas VIII SMPN 1 Bae Kudus. Kelas eksperimen I diterapkan model Discovery Learning dan kelas eksperimen II diterapkan model Inquiry Learning. Teknik analisis data adalah menggunakan uji-t dan uji Mann-Whitney U. Hasil penelitian ini adalah: 1) Pada uji t memberikan taraf signifikansi  Artinya terdapat peningkatan kemampuan literasi matematika peserta didik kelas eksperimen I setelah diterapkannya model Discovery Learning secara signifikan dengan kenaikan N-gain sebesar , 2) Pada uji t memberikan taraf signifikansi  Artinya terdapat peningkatan kemampuan literasi matematika peserta didik kelas eksperimen II setelah diterapkannya model Inquiry Learning secara signifikan dengan kenaikan N-gain sebesar , 3) Pada uji Mann-Whitney U memberikan taraf signifikansi  yang menunjukkan bahwa kemampuan literasi matematika peserta didik lebih meningkat dengan diterapkannya model Discovery Learning daripada Inquiry Learning.